Self-management preferences in patients with mild cognitive impairment: A qualitative study - Jiao, Yuchen; Liu, Chang; Chang, Jing; Zhou, Shiyu; Ji, Yan (Frontiers in Psychology, 2022)
Purpose Patients with mild cognitive impairment (MCI) require self-management, yet current self-management compliance is low. Taking patients’ preferences into account can improve the self-management situation. The purpose of this study is to look into MCI patients’ preferences for self-management in China. Methods A qualitative research was conducted using semi-structured in-depth interviews with 21 patients recently diagnosed with MCI who were chosen by purposive sampling. These interviews were analyzed through thematic analysis and identified emerging themes. Results Five themes of self-management preference were identified: (1) Preference for acquiring disease knowledge; (2) Preference for participating in drug therapy; (3) Preference for participating in exercise; (4) Preference for applying memory compensation strategy; (5) Preferences for emotional expression and response. Conclusion Our study identified the specific preferences of MCI patients in China for the main self-management items. The findings are valuable insights for knowing MCI patients’ self-management content and preferences and provide better guidance for health practitioners to improve self-management compliance.